Translation Studies and Psychoanalytic Transference - Ingram, Susan (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractThis article charts parallel developments in theorizing conceptions of translation and psychoanalytic transference. The place of transference in the psychoanalytic models of Freud, Lacan, Deleuze and Guattari, and Jung is first elucidated and then related to a corresponding view of translation. These possibilities are found to be as theoretically suggestive in terms of providing models of intercultural interaction as the models of transference are in understanding interpersonal interaction. It concludes, with Jung, on a utopian note with a call for cultural coniunctio.